Split Range Control Intended for Portable Chamber Warming Structure - A. , Anie Selva Jothi; B.Singh, Ajith.; V., Rukkumani; S., Sheebarani; K., Shanthi; P., Manju (International Journal of Psychosocial Rehabilitation, 2020)
Modeling of temperature control in various systems on a field is one of the most common problems in industrial environments. In home heating systems also, this comes into existence. First principle modeling of the temperature control process is performed with so much postulation. In this paper, a split-range controller is attempted for room temperature control, which is one of the classic examples of a non-linear system. Room temperature is observed as the input data, and the output voltage to the fan is controlled for this temperature control process. The input temperature is measured using a J-type thermocouple using an analog input port on DAQ cards. While the output voltage is generated for two individual 12v DC fans (suction & discharge) using the analog output port on DAQ cards. The collected data is processed in a split range controller in a virtual instrumentation environment. We have analyzed the setup model of the temperature control process practically using the LabVIEW environment, which provides the outcomes nearly alike to the simulation results of the process. The Split Range Controller is utilized here to control the temperature of the output system using the inputs and the outputs offered. This will produce a gradual control of room temperature under cold conditions and will be mobile so that it can be utilized for a single room alone.